HUBUNGAN SOSIODEMOGRAFI, STATUS KESEHATAN, DAN THEORY OF PLANNED BEHAVIOR DENGAN PENGAMBILAN KEPUTUSAN VAKSINASI COVID-19 PADA IBU MENYUSUI - Dian Puspitasari Effendi; Siti Nurul Hilmi; Herry Novrinda (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2022)
The Ministry of Health has declared that the COVID-19 vaccination is safe for breastfeeding mothers. The COVID-19 vaccine is an effective way to prevent the transmission of COVID19. The status of the COVID-19 vaccine in Banten Province for COVID-19 in the general and vulnerable communities, one of which is breastfeeding mothers for the first dose 48.70%, the second dose 27.82% of the target of 6,877.059. In this picture, it can be seen that vaccine coverage has not met the target for the general and vulnerable population. This study was to determine the relationship between sociodemography, health status, and theory of planned behavior for COVID-19 vaccination decision making in breastfeeding mothers in Banten province. This research was a quantitative design with a cross-sectional study approach. For data collection by link distribution in the province of Banten. Data analysis used univariate analysis to describe sociodemographic characteristics including age, education, marital status, the socio-economic status, number of respondents' children, and bivariate analysis to determine the relationship between variables used chi-square. Based on the results of the study, it shows that from sociodemography only socioeconomic status has a significant relationship in making COVID-19 vaccination decisions. Meanwhile, from health status and the theory of planned behavior including attitude, subjective norms, perceived behavioral control, and self-efficacy are no significant relationship in making COVID-19 vaccination decisions. Conclusion of this study was only the socio-economic status which had a significant relationship in making COVID-19 vaccination decisions in breastfeeding mothers.